Gestaltterapia e experiência religiosa: relação e cura - Santana Filho, Otaviano Bezerra (2014)
The present study aimed to research the religious phenomenon and faith as a dimension of otherness , as well as investigate possible relations with Gestalt therapy dialogue and healing. The research was a phenomenological nature of literature and existential perspective that was founded the works of Martin Buber 's Philosophy of Dialogue and its religious existentialism of the eternal relationship between " I-Thou , I - It and the eternal Thou ." Added to this , also problematized the vision of Rudolf Otto 's numinous and other authors such as Mircea Eliade , Gestalt therapy theorists , Heidegger , Viktor Frankl , among others . Our results and discussions were presented from three dimensions . The first was to focus on the religious phenomenon intimately related to the notion of the experience of otherness . The second step was to search for a possible rapprochement between the thought of Gestalt Therapy and religious experience . Finally , we sought to understand Gestalt Therapy and Spirituality as a space for dialogue and healing.